The Effect of Green Marketing on Purchase Decision with Brand Image as Mediating Variable - Deasy Lestary Kusnandar; Lucky Radi Rinandiyana (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
The purpose of this study is to explain the influence of marketing strategy on purchase decision through brand image as mediation. To test the empirical model, this study used Structural Equation Modeling (SEM) analysis tool. Other analysis tools used include AMOS 21.0, SPSS 16.0 and Microsoft Excel 2007. The number of samples in this study were 140 users of Tupperware in Tasikmalaya. The results of this study indicate that the dimensions of marketing strategy that are green product, green price, green place and green promotion have positive effect on purchase decision and brand image, and brand image mediate the influence of marketing strategy dimensions on purchase decision.